2011
DOI: 10.1002/job.768
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and work behaviors: The mediating role of LMX

Abstract: Summary We investigated the mediating role of the leader–member exchange (LMX) in the association of abusive supervision and employee work behaviors (task performance and organizational citizenship behaviors toward the organization and individuals). Using data collected from 366 supervisor–subordinate dyads, we found that LMX fully mediated the negative effects of abusive supervision on all three work behaviors. In addition, we conducted a supplementary study on the basis of the data collected from 54 supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
205
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(216 citation statements)
references
References 63 publications
7
205
0
4
Order By: Relevance
“…Drawing on social exchange theory, researchers argue that abusive supervision decreases the quality of social exchange between subordinates and supervisors (Xu et al, 2012). Subordinates may withdraw their work-related effort if they perceive they have been treated unfairly by their supervisors (Liu & Wang, 2013).…”
Section: Abusive Supervision and Subordinate Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on social exchange theory, researchers argue that abusive supervision decreases the quality of social exchange between subordinates and supervisors (Xu et al, 2012). Subordinates may withdraw their work-related effort if they perceive they have been treated unfairly by their supervisors (Liu & Wang, 2013).…”
Section: Abusive Supervision and Subordinate Performancementioning
confidence: 99%
“…Extant studies have documented that abusive supervision leads to psychological distress (Harvey, Stoner, Hochwarter, & Kacmar, 2007), low organizational commitments and job satisfaction (Tepper, 2000), workplace deviance (Lian, Ferris, & Brown, 2012b;Thau, Bennett, Mitchell, & Marrs, 2009), low individual and group performance (Priesemuth, Schminke, Ambrose, & Folger, 2014;Xu, Huang, Lam, & Miao, 2012), less helping behavior (Peng, Schaubroeck, & Li, 2013), low levels of creativity (Liu, Liao, & Loi, 2012), and family conflicts (Hoobler, & Brass, 2006). Such negative effects annually yield approximate $23.8 billion cost for US organizations (Tepper, Duffy, Henle, & Lambert, 2006).…”
mentioning
confidence: 96%
“…As these both countries are totally different from each other on the basis of their economic situation, religion and especially on their cultural grounds. Aryee, Chen, Sun, & Debrah, 2007;Jian et al, 2011;Wang et al, 2012;Wei & Si, 2013;Xiaqi, Kun, Chongsen, & Sufang, 2012;Xu, Huang, Lam, & Miao, 2012) 2 North America (Tepper, 2000;Tepper 2007;Tepper et al, 2009;Tepper et al, 2006;Tepper, Duffy, Hoobler, & Ensley, 2004;Tepper, Duffy, et al, 2001;Tepper et al, 2008;Tepper, Lockhart, & Hoobler, 2001;Tepper et al, 2011;Tepper et al, 2007;Ashforth, 1994Ashforth, , 1997Bowling & Michel, 2011;Carpenter, Geletkanycz, & Sanders, 2004;Christmas, 2007;DelBel, 2003;Dupré, Inness, Connelly, Barling, & Hoption, 2006;Namie & Namie, 2009;Tsapatsis, 2012) 3 Australia (Grice et al, 2003 ;Ng, 2010 ;Kiazad et al, 2010) 4 United Kingdom (Turnbull, 1995;Deborah, 2000;McMillan, 1995) 5 Pakistan , Khan, 2010Khan, 2014aKhan, , 2014bKhan, , 2014cImran, 2010;Mukhtar et al, 2010;Bashir & Hanif, 2011;Gadit & Mugford, 2008) 6 Israel (Dana Yagil, 2006) 7 Turkey …”
Section: Selection Of Hofstede's Cultural Dimensions For Present Studymentioning
confidence: 99%
“…Prior research has suggested that leaders and followers have different expectations of each other (Xu et al, 2011). For example, Chinese employees usually expect a leadership style where the leader maintains a harmonious relationship with followers while being directive (Hsu, 1982), whereas employees from Western Europe, Scandinavian countries and North America, characterised by high individualism, tend to support participative management processes (Hofstede, 1980;Smith & Peterson, 1988;Dorfman et al, 1997).…”
Section: Background and Development Of The Lmx Theorymentioning
confidence: 99%
“…If one person accepts an offer from another, and reciprocates a satisfactory response, the process continues in this way, resulting in high-quality relations over time (Cogliser et al, 2009). Employees who feel that they benefit from their leader will try to reciprocate by offering a favour in return (Xu et al, 2011). Therefore, a leader can take advantage of this phenomenon by doing a favour ahead of the employees, such as volunteering to give more resources or offering professional support and rewards, to encourage employee work performance.…”
Section: Background and Development Of The Lmx Theorymentioning
confidence: 99%